2022
DOI: 10.5772/intechopen.99810
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Inputs Parameters Used to Estimate Enteric Methane Emission Factors Applying a Tier 2 Model: Case Study of Native Cattle in Senegal

Abstract: In the context of the Paris Agreement, and considering the importance of methane emissions from cattle in West Africa, application of a Tier 2 method to estimate enteric methane emission factors is clearly pertinent. The current study has two purposes. Firstly, it aims to detect how much each input parameter contributes to the overall uncertainty of enteric methane emission factors for cattle. Secondly, it aims to identify which input parameters require additional research efforts for strengthening the evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This intricate web of elements contributes to the difficulties in accurately estimating emissions [29,74,75]. The identified uncertainties in animal parameters highlight the urgency of addressing the challenges to refine emission models and devise effective mitigation strategies [48,68,75]. The present study underscores the significance of improv-ing precision in data collection, advancing modeling techniques, and cultivating a holistic understanding of the diverse factors influencing emissions [74].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This intricate web of elements contributes to the difficulties in accurately estimating emissions [29,74,75]. The identified uncertainties in animal parameters highlight the urgency of addressing the challenges to refine emission models and devise effective mitigation strategies [48,68,75]. The present study underscores the significance of improv-ing precision in data collection, advancing modeling techniques, and cultivating a holistic understanding of the diverse factors influencing emissions [74].…”
Section: Discussionmentioning
confidence: 88%
“…Utilizing both top-down and bottom-up methods, as highlighted by Kumari et al [71] and Vechi et al [73], introduces complexities and uncertainties in assessing methane emissions. Additionally, the impact of assumptions in LCA and default parameters in IPCC Tier 2 methodology, emphasized by Xu et al [63] and Ndao et al [68], further contributes to the overall uncertainty in emission factor accuracy. Hempel et al [70] draw attention to the limitations of livestock population databases and the potential overestimation of emissions using default factors, underscoring the need for improved data coverage and parameter refinement.…”
Section: Quantification and Estimation Approaches And Techniques Used...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Tier 1 method uses fixed, default emission factors (EFs) (19) to compute emissions per head of livestock. Tier 1 EFs for SSA are based on modeling studies, and more recent in situ research has shown that IPCC Tier 1 EFs may not be appropriate for livestock in SSA (20)(21)(22)(23)(24)(25). Moreover, because it relies on fixed EFs, the Tier 1 approach cannot capture trends in emissions over time due to changes in management or other factors (26) and is therefore not suitable for measurement, reporting, and verification (MRV) purposes and tracking progress toward mitigation goals outlined in NDCs.…”
Section: Introductionmentioning
confidence: 99%